(untitled) (Heritage, 2023)
Young people who study physical education are regarded as having proper body structure and composition. Therefore, this study aimed to evaluate the status of some anthropological segments in male PE students (N-30) aged 18 – 39 years. Methods. Cross-sectional study design. In addition to age (22.39±5.35), the essential anthropometric variables were estimated: body height (183.72±7.65), body weight (82.88±9.93), and body composition parameters: BMI (24.61±2.94), body fat (19.85±6.47), visceral fat (6.03±3.01), skeletal muscles (39.45±3.92), resting metabolism rate (1812.63±134.61), and Health Status: systolic blood pressure (132.87±19.31), diastolic blood pressure (74.2±13.23), and resting heart rate (76.50±14.93). Descriptive statistics are presented in Tables (1-8), and with the graphical presentation in Histograms (1-10). Testing was performed during Summer Outdoor activities (field classes) on-site at Gazivode Lake (Kosovo). Results - presented as comparative analysis within male PE students and selected Profile model, regarding the estimated Min-Max results and calculated mean value (average). The comparative analysis points to some within-sample differences. However, the results of PE male students are on the border of typical values in most parameters, except for Age and Basic anthropometry. Discussion compares previously established studies with the specifically selected samples of participants and the actual PE male students. Conclusion. All of the results indicate that body fat values are higher than those favorable for the PE students, which can be due to inadequate nutrition or physical activity level, and even the reason may lie in insufficiently high criteria for enrollment in PE studies.